IR BEDIL Bergedil-Stuffed Taufu / Abdul Razi Abdul Rashid and Muhammad Izzudin Anuar - Abdul Rashid, Abdul Razi; Anuar, Muhammad Izzudin (2021)
IR BEDIL is food business that established 10 November 2021 with two partners which are Abdul Razi and Muhammad Izzudin. This business is selling stuffed food or known as bergedil in Malaysia. The idea was come from Abdul Razi when he helped his mother making bergedil and sell it to the neighbour. From that, he got an idea to develop the business by using social media. So, we created Facebook page on 29 November 2021. The main idea for this online business is to sell the stuffed tofu around Malacca. For those who was interest to buy stuffed tofu, they can text us by WhatsApp and the stuffed tofu will delivered to their house. We also have a variable flavour for our stuffed such as chicken, meat, shrimp, and potato. With variable flavour, the customer can choose the ones that they enjoy to eat. Our target market is for the food lover. This stuffed food can eat by all age categories because it is one of the healthy foods. So, everyone in Melaka can buy our stuffed food anytime and anywhere. IR BEDIL Facebook page now has 24 followers only because we are still new in Facebook platform. This page is used to promote our product which is stuffed tofu and other information that can give benefits to the reader. This Facebook Page was manage by Muhammad Izuddin, and this platform is very good to entrepreneur because it helps seller to communicate with the customer and promote our product to people. Using this platform, we manage to set up our promoting strategy by providing 16 hard sell, 16 soft sell and seven teasers. We also prepared a schedule posting on Facebook and explanation about every posting in Facebook Page.